MODERN PATHOGENETIC ASPECTS OF BLEACHING DISPLAYS OF MAMMARY GLAND - Безнощенко, Галина Борисовна; Кравченко, Елена Николаевна; Кропмаер, Кирилл Петрович; Макаркина, Людмила Геннадьевна; Гуртавлева, Ксения Сергеевна (Mother and Baby in Kuzbass, 2018)
The prevalence of benign dysplasia of mammary glands in our time is unprecedentedly high. Even in the most «protected» cohort, in women with a large number of births and a long experience of breastfeeding, these benign processes are found in every fifth patient. Mastopathy is found in 60-80 % of women. In this case, the pathogenetic aspects of this disease remain quite controversial to this day [1].